23PA new quercetin glycoside enhances TNBC immunological profile through TP53/miR-155/MICA/ULBP2. (7th November 2019) - Abdel-Latif, M; Afifi, A; Soliman, R; Elkhouly, A; Abdelmotaal, A; Youness, R A
Abstract: Background: Triple-negative breast cancer (TNBC) patients are the least fortunate in terms of prognosis and treatment. Yet, the advent of immunotherapy has opened the gateway for several hopes. The most prominent immuno-oncological strategy is the utilization of the adaptive immune system through immune checkpoint inhibitors. But unfortunately evidence of resistance has shown up in TNBC patients. Consequently, as an alternative approach researchers have thought about employing the innate arm of the immune system through potentiating natural killer (NK) cells cytotoxicity. The most activating downregulated immune-ligands on TNBC cells are MHC class I polypeptidesequence A (MICA) and UL-16 binding protein 2 (ULBP2). Recently, nutraceuticals provided a promising avenue in oncology. Our group has recently isolated a new quercetin glycoside (3′-methoxy-3-O-(4″-acetylrhamnoside)-7-O- α-rhamnoside) from Cleome droserifolia, which displayed a potent antitumor activity against colorectal and liver cancers through TP53. However, this has never been investigated in terms of TNBC. The aim of this study is to examine the impact of quercetin glycoside on TP53 /miR-155 axis and its validated downstream immune ligands MICA and ULBP2. Methods: MDA-MB-231 and MCF-7 cells were cultured. Quercetin glycoside was isolated from Cleome droserifolia. Serial dilutions were used for treatment. IC50 value was determined using MTT and trypan blue assays. Biazol was used for RNA extraction. Reverse transcription was performed. Expression profiles were determined via q-RT-PCR. Results: The quercetin glycoside showed a significant dose-dependent decrease in MDA-MB-231 proliferation and viability. IC50 is 12.5 μM. MICA and ULBP2 was found to be markedly under-expressed in MDA-MB-231 compared to MCF- 7. While upon treating MDA -MB-231 cells with the Quercitin Glycoside, this resulted in a marked induction in the expression of TP53 and repression of its downstream miR-155. This was further corroborated by the striking upregulation of miR-155 validated targets MICA (7 folds) and ULBP2 (2 folds). Conclusions: A novel quercetin glycoside haltsTNBC progression and improves the immunogenic profile of MDA-MB-231 cells through TP53/miR-155/MICA/ULBP2 axis. Legal entity responsible for the study: German University in Cairo. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.